Transjugular Intrahepatic Portosystemic Shunt for Acute Variceal Bleeding: A Meta-analysis. Issue 6 (July 2015) - Qi, Xingshun; Jia, Jia; Bai, Ming; Guo, Xiaozhong; Su, Chunping; García-Pagán, Juan C.; Han, Guohong; Fan, Daiming
Abstract : Background and Aims: Acute variceal bleeding is the most common lethal complication of liver cirrhosis. A meta-analysis was conducted to compare the outcomes of transjugular intrahepatic portosystemic shunt (TIPS) to those of medical/endoscopic therapy for acute variceal bleeding in cirrhotic patients. Methods: The PubMed, EMBASE, and Cochrane Library databases were searched for all relevant comparative studies. Odds ratios (OR) and hazard ratios (HR) with 95% confidence intervals (CI)were pooled for dichotomous and time-dependent variables, respectively. Subgroup analyses were performed according to the type of study design (randomized or nonrandomized studies), source of bleeding (esophageal or gastric varices), type of stent (covered or bare stent), and patient selection (high risk or unselected patients). Results: Six papers were eligible. TIPS was superior to medical/endoscopic therapy in decreasing the incidence of treatment failure (OR=0.22; 95% CI, 0.11-0.44), improving overall survival (HR=0.55; 95% CI, 0.38-0.812), and decreasing the incidence of bleeding-related death (OR=0.19; 95% CI, 0.06-0.59). Although TIPS did not significantly decrease the incidence of rebleeding (OR=0.27; 95% CI, 0.06-1.29), it became significantly greater in the subgroup meta-analyses of randomized studies (OR=0.09; 95% CI, 0.03-0.32) than in those of nonrandomized studies (OR=0.76; 95% CI, 0.40-1.45; subgroup difference, P =0.003), and in the subgroup meta-analyses of studies including high-risk patients (OR=0.06; 95% CI, 0.01-0.23) than in those including low-risk patients (OR=0.83; 95% CI, 0.44-1.56; subgroup difference, P =0.0007). In addition, TIPS did not significantly increase the incidence of posttreatment hepatic encephalopathy (OR=1.37; 95% CI, 0.63-2.99). Conclusions: With the exception of the benefit of prevention from treatment failure, TIPS with covered stents might improve the overall survival of high-risk patients with acute variceal bleeding. Abstract : Supplemental Digital Content is available in the text.